2019
DOI: 10.1093/conphys/coz017
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the sub-lethal impacts of plastic ingestion by shearwaters using fatty acid analysis

Abstract: Our study is the first to describe the fatty acid composition of the liver, breast muscle, and adipose tissue from flesh-footed (Ardenna carneipes) and short-tailed shearwaters (A. tenuirostris) and uses this technique to explore possible sub-lethal effects of plastic ingestion on these species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…To date, studies of the effect of plastic debris on wildlife have been largely confined to quantifying plastic burden (e.g., Provencher, et al 53 ), or relating that burden to gross measures of body condition, such as mass or chick size (e.g., Lavers, Bond and Hutton 6 ). Though these studies remain important, increasingly, the potential for sublethal impacts on birds' physiology is of concern 54 , including the presence of toxic chemicals 6,15,55 , harmful microbiota 56,57 , and the ubiquity of small particles which can be distributed throughout the digestive tract 21,58 . Such relationships have been recently described in marine invertebrates and fish 59,60 , but few data exist for seabirds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, studies of the effect of plastic debris on wildlife have been largely confined to quantifying plastic burden (e.g., Provencher, et al 53 ), or relating that burden to gross measures of body condition, such as mass or chick size (e.g., Lavers, Bond and Hutton 6 ). Though these studies remain important, increasingly, the potential for sublethal impacts on birds' physiology is of concern 54 , including the presence of toxic chemicals 6,15,55 , harmful microbiota 56,57 , and the ubiquity of small particles which can be distributed throughout the digestive tract 21,58 . Such relationships have been recently described in marine invertebrates and fish 59,60 , but few data exist for seabirds.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies of the effect of plastic debris on wildlife have been largely confined to quantifying plastic burden (e.g., Provencher et al) or relating that burden to gross measures of body condition, such as mass or chick size (e.g., Lavers, Bond, and Hutton). Though these studies remain important, increasingly, the potential for sublethal impacts on birds’ physiology is of concern, including the presence of toxic chemicals, ,, harmful microbiota, , and the ubiquity of small particles which can be distributed throughout the digestive tract. , Such relationships have been recently described in marine invertebrates and fish, , but few data exist for seabirds. This is concerning as birds can compensate for physiological impairments caused by disease or other stressors meaning they can appear healthy for a period of time, which can be misleading when undertaking visual assessments of health and condition or using superficial measures, such as body size.…”
Section: Discussionmentioning
confidence: 99%
“…80-90 days old) and followed the recommended protocol for quantifying plastic in seabird necropsies (van Franeker, 2004). Ingested plastic items including micro-plastic (>1 µm; Barnes et al, 2009) and visible macro-plastic (> 5mm diameter; Provencher et al, 2017), from the proventriculus and gizzard were categorised by type and colour following Provencher et al (2017), with a minor modification to the colour categories in order to be consistent with a longterm monitoring study of Australian Procellariiformes (Lavers and Bond, 2016b;Puskic et al, 2019). Plastic items were dried and weighed to the nearest 0.001 g using an electronic balance.…”
mentioning
confidence: 99%
“…The authors found associations between ingested plastic and morphometrics and blood calcium (significant, declining trends with more ingested plastic) as well as uric acid, cholesterol, and amylase production (increasing levels with more ingested plastic), and concluded analysis of physiological parameters is critical to better understanding the sublethal impact of plastic debris. Puskic et al (2019) took a similar approach and investigated potential sublethal impacts to Flesh‐footed ( Ardenna tenuirostris and Short‐tailed Shearwaters ( A. carneipes ), focusing on fatty acid analysis for the connection to energy usage; while the study did not find a relationship between fatty acids and ingested plastic, it furthered the concept of investigating sublethal impacts.…”
Section: Effects Of Microplastic Debrismentioning
confidence: 99%